1984
DOI: 10.1007/bf00379629
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope ratio as a tracer of mangrove carbon in Malaysian ecosystems

Abstract: The ratio of stable carbon isotopes (δC) in plants and animals from Malaysian mangrove swamps, coastal inlets, and offshore waters was determined. Vascular plants of the swamps were isotopically distinct ( x±s.d.=-27.1±1.2‰) from plankton (-21.0±0.3‰) and other algae (-18.7±2.2‰). Animals from the swamps (-20.9±4.1‰) and inlets (-19.8±2.5‰) had a wide range of isotope ratios (-28.6 to-15.4‰), indicating consumption of both mangrove and algal carbon. Several commercially important species of bivalves, shrimp, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
135
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(166 citation statements)
references
References 35 publications
22
135
2
3
Order By: Relevance
“…In general, data on δ 13 C and δ 15 N from the present study is comparable to that reported by Rodelli et al (1984). The carbon isotope signature (δ 13 C) of consumers can reveal the relative contribution of a diet as potential primary sources in a trophic network.…”
Section: Figuresupporting
confidence: 88%
“…In general, data on δ 13 C and δ 15 N from the present study is comparable to that reported by Rodelli et al (1984). The carbon isotope signature (δ 13 C) of consumers can reveal the relative contribution of a diet as potential primary sources in a trophic network.…”
Section: Figuresupporting
confidence: 88%
“…δ 13 C mangrove were isotopically lighter compared to standards and ranged between −26.09 and −29.08, suggesting a Calvin mechanism (C3) of photosynthesis. These values are comparable to those of the Rhizophora mangroves of Malaysia [36], Sri Lanka [37] and Tanzania [38]. Carbon pools, on per hectare basis were highest in site A, the freshwater stands, while lowest values were in the degraded forests of site B.…”
Section: Carbon Storage Potentialssupporting
confidence: 70%
“…Mangrove ecosystems support essential ecological functions such as intercepting land-derived nutrients, pollutants and suspended matter before these contaminants reach deeper water (Marshall 1994, RiveraMonroy and Twilley 1996, Tam and Wong 1999. Mangroves also perform other important services, such as preventing coastal erosion by stabilizing sediments (Marshall 1994, Tam andWong 1999), furnishing nursery and spawning areas for commercially important coastal fish and shellfish species (Rodelli et al 1984, Sasekumar et al 1992, and providing stopover sites for migratory birds, fish, and mammals (Saenger et al 1983). Any loss of mangrove forest, therefore, means a loss of their important contributions to subsistence uses, and to ecological, economic, and conservation functions (Valiela et al 2001).…”
Section: Introductionmentioning
confidence: 99%